Study on the methodology for the quantification of carbon dioxide in wine using a quartz crystal microbalance - Gomes, MT
A new method for carbon dioxide (CO2) determination in wine is proposed, based on the use of a quartz crystal microbalance. The analytical experimental set-up was made in the laboratory, and the methodology, free of interference and with an easy calibration procedure, is adequate to monitor CO2 in wine.